Synthesization and optical characterization of photovoltaic materials for perovskite solar cell application. Issue 1 (March 2021) - Dongre, Y K; Roy, P; Khare, A; Tiwari, S
Abstract: The performance of Perovskite solar cells (PSCs) has rapidly increased over the last decade. The power conversion efficiency (PCE) of 25.2% has been reported. Drastic and rapid change in PCE of PSCs has attracted a lot of attention toward this alternative photovoltaic technology that can be manufactured using simple and low cost processing techniques, over the traditional silicon solar technology. Here in this work, we have synthesized Molybdenum trioxide (MoO3 ) and Titanium dioxide (TiO2 ) for charge transport materials application in PSC application. The analysis of materials has been carried out by photoluminescence and absorbance spectra. The results signify that MoO3 has absorbed at the visible region around (600-800) nm and the absorbance of TiO2 tuned at 400 nm. Due to high absorption range (600-800) at visible region MoO3 is suitable for Hole Transport Material (HTM). The widely used Electron Transport Material (ETM) TiO2 is also synthesized and characterized.